Antibacterial Activity of Different Extract of Medicinal Plant Antirrihnum Orontium. - Himayat Ullah; Shehzad Saleem; Wisal Ahmad; Muhammad Hanif; Zahid Ali; Muhammad Israr (Faculty of Pharmacy, Universitas Mulawarman, Samarinda, Indonesia, 75117, Gedung Administrasi Fakultas Farmasi Jl. Penajam, Kampus UNMUL Gunung Kelua, Samarinda, Indonesia, 2020)
Antirrhinum Orontium is belonging to the family Plantaginacea commonly known as lesser snapdragon which is a flowering plant belong to genus Antirrhinum. It was traditionally used in treatment of Tumor, Eye inflammation and Ulcer. Antirrhinum Orontium is contain mostly tertiary alkaloids bases one of them is identified as 4-methyl-2, 6-naphthyridine and Choline is identified as quaternary base. The recent study is to investigate the antibacterial activity of Ethyl acetate, Dichloromethane, Hexane and Water extracts of Antirrhinum Orontium, against the pathogen like Escherichia coli and Staphylococcus aureus. Both the Soxhlet and Maceration water extract were found most active from the other extract against Escherichia coli and Staphylococcus aureus by using agar well diffusion method. The measured zone of inhibition for Soxhlet water extract is 21±0.05mm and Maceration water extract is 20±0.05mm against gram positive Staphylococcus aureus, while for gram negative Escherichia coli 23±0.05mm is measured for Soxlet and 21±0.05mm measured for Maceration water extracts